Biomass and abundance of termites in three remnant areas of Atlantic Forest in northeastern Brazil - Vasconcellos,Alexandre (2010)
Termite biomass and abundance were estimated in three remnant areas of Atlantic Forest in northeastern Brazil: Reserva Biológica de Pedra Talhada-RBPT (Alagoas State), Parque Estadual Dois Irmãos-PEDI (Pernambuco State), and Área de Proteção Ambiental Mata do Buraquinho-APMB (Paraíba State). A quantitative sampling of the termite assemblages present on trunks and leaf litter, in nests, and in the soil was undertaken during the months of June and July (rainy season) and November and December (dry season) of 2000. Thirty seven species of termites were encountered and quantified in the three remnant forest areas. The termite biomass varied from 10.09 to 11.30 g (fresh weight)/m² and abundance varied from 4911 to 5663 individuals/m². The subfamily Nasutitermitinae was dominant in terms of the number of species, biomass, and abundance. The soil-feeders were the most abundant at the three sites, while wood-feeders had the largest biomass at least at the PEDI and APMB sites. Among the microhabitats quantified, termites were most frequently encountered in the soil, being most heavily concentrated at depths of 0-20 cm. Two species stood out in terms of their biomass and abundance: Embiratermes parvirostris Constantino, on the soil, and Nasutitermes corniger (Motschulsky), on decomposing trunks and in nests. Estimates of biomass and abundance suggest that termites play an important role in the decomposition of the plant necromass in remnant forest areas of the Atlantic Forest in northeastern Brazil.